ORGANIZATIONAL CULTURE AND WORK DISCIPLINE IN IMPROVING EMPLOYEE PERFORMANCE AT THE SECRETARIAT OF THE REGIONAL HOUSE OF REPRESENTATIVES OF LAMPUNG PROVINCE - Muhammad Taufiq Ajoyasa; Ida Farida (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes organizational culture in work discipline as an effort to improve employee performance at the Secretariat of the Lampung Provincial DPRD. The study was motivated by variations in employee discipline, uneven internalization of organizational values across work units, and the need for more consistent performance control. A qualitative descriptive approach was used. Data were collected through in-depth interviews, direct observation, and documentation involving leaders and employees who understood the implementation of organizational culture and work discipline. Data validity was strengthened through source, method, and time triangulation as well as member checks, while analysis followed data reduction, data display, and conclusion verification. The findings show that organizational artifacts, integrity, responsibility, professionalism, teamwork, basic assumptions about discipline, and professional work ethics support the development of disciplined behavior and better performance. However, inconsistent enforcement of rules, unequal perceptions of fairness, limited two-way communication, and leadership practices that are not fully consistent remain obstacles. Strengthening organizational values, fair rule enforcement, exemplary leadership, and continuous evaluation are therefore required to sustain employee discipline and performance.